Keberlanjutan Demokrasi Indonesia? Dua Tahun Pandemi COVID-19 yang Penuh Tantangan - Agustino, Leo; Hikmawan, M Dian; Silas, Jonah (HK-Publishing, 2023)
AbstractThe COVID-19 pandemic provides trials as well as lessons for the democratic system in Indonesia. This article examines and discusses the sustainability of democracy in Indonesia by reflecting on the handling of the COVID-19 pandemic. The research method we use is qualitative with data collection techniques through observation, library research, and utilizing various online sources to analyze it. Our findings show that the government's strategy in anticipating the COVID-19 pandemic has reduced the level of democracy. This can be seen in the politicization of regulations which has led to the arrest and prosecution of civilians who disagree with the government. Second, the occurrence of executive aggrandisement by attracting opposition elites into the government so that there is no resistance in terms of handling COVID-19 and, third, the birth of a discourse on the perpetuation of executive power. If there are no efforts to correct the course of democracy, then Indonesian democracy will experience a deeper setback than during the COVID-19 pandemic.Keywords: COVID-19, Executive Aggrandisement, Democratic Regression, Authority AbstrakPandemi COVID-19 memberikan cobaan sekaligus pembelajaran terhadap sistem demokrasi di Indonesia. Artikel ini membahas dan mendiskusikan keberlanjutan demokrasi di Indonesia dengan bercermin pada penanganan pandemi COVID-19. Metode penelitian yang kami gunakan adalah kualitatif dengan teknik pengutipan data melalui observasi, library research, serta memanfaatkan berbagai sumber online untuk menganalisisnya. Temuan Kami menunjukkan bahwa strategi pemerintah dalam mengantisipasi pandemi COVID-19 telah menurunkan kadar demokrasi. Ini tampak pada politisasi regulasi yang berujung pada penangkapan dan penuntutan warga sipil yang berseberangan pandangan dengan pemerintah. Kedua, terjadinya executive aggrandisement dengan cara menarik menarik masuk elit oposisi dalam pemerintahan agar tidak ada perlawanan dalam hal penanganan COVID-19 dan, ketiga, lahirnya wacana pengekalan kekuasaan eksekutif. Jika tak ada upaya koreksi atas jalannya demokrasi, maka demokrasi Indonesia akan mengalami kemunduran yang lebih dalam dari masa pandemi COVID-19 lalu.Kata Kunci: COVID-19, Executive aggrandisement, Regresi demokrasi, Kuasa